2015
DOI: 10.1007/s00101-015-0093-8
|View full text |Cite
|
Sign up to set email alerts
|

„Hämoglobinorientierter und gerinnungsfaktorbasierter Algorithmus“

Abstract: The SOP based on coagulation factor values and standardized clotting therapy showed a clear trend to reduction of the SMR in massively transfused trauma patients. On the other hand the SOP achieved a significant reduction in the transfusion requirements and a significant improvement in the hemostatic results in the most severely injured patients. This can be interpreted as an effective use of coagulation factors in the early hospital treatment of trauma patients with ongoing bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…There is increasing interest in the use of goal-directed strategies guided by either POC VEM [543549] or CCAs [522, 550] to augment DCR during the acute care of bleeding trauma patients [551554]. A recent survey among surgeons and anaesthesiologists in Germany revealed that 90% used CCA to guide decision-making in the diagnosis and treatment of bleeding trauma patients, whereas 56% reported that they also used extended VEM such as ROTEM® or TEG® [555], and this predominantly in advanced trauma centres [556].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing interest in the use of goal-directed strategies guided by either POC VEM [543549] or CCAs [522, 550] to augment DCR during the acute care of bleeding trauma patients [551554]. A recent survey among surgeons and anaesthesiologists in Germany revealed that 90% used CCA to guide decision-making in the diagnosis and treatment of bleeding trauma patients, whereas 56% reported that they also used extended VEM such as ROTEM® or TEG® [555], and this predominantly in advanced trauma centres [556].…”
Section: Resultsmentioning
confidence: 99%
“…In the intention-to-treat analysis, all-cause 28-day mortality was 5/35 (14.3%) in the laboratory-result-guided transfusion group versus 13/40 (32.5%) in the group that was treated according to the fixed-ratio 1:1:1 protocol [RR 2.27 (95% CI 0.98–9.63)]. The introduction of a novel standard operating procedure (SOP) using a Hb/CCA-oriented and coagulation-factor-based algorithm for the early correction of trauma-induced coagulopathy in patients requiring a massive transfusion was retrospectively assessed using a pre- and post-implementation approach at a single centre in Germany [550]. The main objective was the effect on transfusion requirements and the standardised mortality ratio (SMR), which is the ratio of observed deaths to expected/predicted deaths.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there is no universal recommendation backed by large evidence how to include specific factor concentrates (e.g., prothrombin complex concentrates [PCC]) or single coagulation factors products (fibrinogen [FI], FVII), within these algorithms. Keeping that in mind, multiple but mostly retrospective data indicate an overall benefit of goal-directed resuscitation and transfusion strategies using global coagulation testing approaches guided either via VHA 34 35 or CCT monitoring 36 37 over DCR in bleeding trauma patients. Interestingly, these studies suggest that (besides all limitations of CCT-monitored strategies like longer turnaround times compared with bedside VHA and missing information on clot formation dynamics and lysis) they might be superior to the use of fixed-ratio methods.…”
Section: Scenario 1: Coagulopathy Following Major Trauma: Goal-direct...mentioning
confidence: 99%